2017
DOI: 10.18203/2320-1770.ijrcog20170380
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of massive obstetric haemorrhage and its materno fetal outcomes in a tertiary care centre

Abstract: Background: Massive obstetric haemorrhage is defined as blood loss of >1500 ml, or a decrease in haemoglobin>4 gm/dl or acute transfusion requirement of >4 units of blood when need for further transfusion is foreseeable. The purpose of this study is to analyse the demographic, medical and obstetric risk factors for massive obstetric haemorrhage and it’s materno fetal outcomes.Methods: Criteria for patient selection was all patients who had an acute obstetric haemorrhage necessitating a transfusion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…2 An Indian study conducted in 2015 reported the incidence of MOH to be 5.7/1000 births. 3 According to WHO, nearly 5 women die every hour in India from complications developed during childbirth , with heavy blood loss caused by haemorrhage being a major factor.…”
Section: Introductionmentioning
confidence: 99%
“…2 An Indian study conducted in 2015 reported the incidence of MOH to be 5.7/1000 births. 3 According to WHO, nearly 5 women die every hour in India from complications developed during childbirth , with heavy blood loss caused by haemorrhage being a major factor.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, more precise and appropriate strategies of prediction and preparation should be developed with the purpose of avoiding these adverse obstetrical outcomes [3,4]. Massive placenta previa hemorrhages occurs either in the operative or in the postoperative period [5]. Consequently, strategies for prediction and prevention of intra-and postoperative hemorrhages are required.…”
Section: Introductionmentioning
confidence: 99%